Legibility of historic district in Kuala Lumpur City Centre, Malaysia - Tan, Lai Kum (2013)
Legibility emphasizes on visibility of physical elements as interpreted by observers. Legible elements comprised of paths, edges, nodes, landmarks and district are found to influence how people identify the structure of a city. These elements are important to create city image and coherent environmental setting. However, historical districts particularly in the centre of the city are threatened by new and unfit development. This affects the unity and harmony of the physical forms and appearance which can be resulted in the weakening of image and identity of urban places. This study intends to examine Lynch's concept of legibility in the context of historical district in Kuala Lumpur city centre. The objectives of the study are to identify legible elements within demarcated district from the people's identification and to understand the influencing factors. Analysis of documentations and archival records together with direct observation of the historical district were done to examine the characteristics of the historical district and the constituting elements. Interviews with mental mapping and questionnaire survey were conducted to elicit the people's identification of the elements considered as legible. The research found that paths and landmarks are among the most recognizable elements identified by the respondents while, edges and nodes are less identifiable. Besides, it is evident that spaces, activities and historical factors influence the people's identification of physical features. The research suggests further study on the role of spaces, activities and historical elements in influencing the legibility of the city of Kuala Lumpur. The findings support the need to preserve identifiable elements such as landmarks and nodes in historical areas and therefore making urban spaces more recognisable as attraction areas for tourism.